SCAPHOID OSTEONECROSIS: AN UNUSUAL SITE FOR OSTEONECROSIS - Günşah Şahin; Özlem Bölgen Çimen; Selda Bağış; Hayal Güler (Archives of Rheumatology, 2000)
Osteonecrosis is defined as the death of bone from repeated interruptions or a single massive interruption of the blood supply to the bone. In this article, we presented a 60 year old woman diagnosed as having polymyalgia rheumatica who developed scaphoid osteonecrosis because of taking corticosteroid for long period. The patient was reported because of unusual localisation for osteonecrotic bone involvement.